Gods ServantÂ as potential local supportÂ : an effort of getting to zero HIV and AIDSÂ In East Nusa TenggaraÂ Indonesia - Manurung, Imelda F.E. (Humanistic Network for Science and Technology (Address: Cemara street 25, Ds/Kec Sukorejo, Ponorogo, East Java, Indonesia 63453), 2018)
The trustinGods servant is influenced by the individuals perception of the reputation of the Gods servant. Reputation is an attribute given to Gods servant based on information from other sources. Reputation isimportant to build individualâstrust in Gods servant whenindividual hasno personal experience regarding the service of Godâs servant. Positive information about Gods servant can reduce the perception of risk of insecurity during service. This can help increaseindividual trustin Godâs servantâscompetence, goodwill and integrity. The trust obtained from an individualbecomes Godâs servantâs potential capital to identify individuals at risk of HIV and AIDS, providesupport to doVCT so that treatment can be promptly given, as well as prevent contagion and early mortality. Therefore, it is necessary for the government to involve Godâs servantsas a potential local support in achieving getting to zero HIV and AIDS